(untitled) (Research, Society and Development, 2020)
The leaves of mangabeira are popularly used in the preparation of teas and infusions for medicinal purposes. Herbal infusions have beneficial properties due to the bioactive substances that act as antioxidants. Thus, the objective of this study was to evaluate the physical-chemical characteristics and the content of nutraceutical bioactive compounds and to verify the influence of time on mango leaf infusions. The infusions were prepared in triplicate at 5 and 10 (I5 and I10) minutes, adding 1 g of vegetable material in natura in 50 mL of boiling water. Analyzes were carried out for physical-chemical characterization of fresh leaves, infusions and residues: color and browning index (I.E.); total soluble solids in ºBrix e; pH. The analyzes of the bioactive compounds were: chlorophylls, carotenoids and total phenols. In the physical-chemical analyzes, the content of total soluble solids did not vary significantly, indicating that the analyzed times extracted similar contents. I.E. remained constant, indicating that heat treatment was not associated with enzymatic activation and browning. However, the infusion time significantly affected phytochemicals. The values ​​of total chlorophyll and its fractions varied with a progressive decrease compared to leaf in natura at different infusion times, as well as total carotenoids, β-carotene and phenols, which suggests the influence of time on the amount of these compounds present in infusions, being that, I5 provided less loss of the compounds compared to I10, being able to correlate positively with the concentration of flavonoids and with the antioxidant activity.